THE ANALYSIS OF THE SUPPORT SERVICES FOR ROHINGYA REFUGEES IN ACEH - Aghisna (IPEM 16 UMY 229, 2016)
This research aims to analyze how the provincial government of Aceh provide the basic needs for the Rohingya refugees to meet the standards of United Nations High Commissioner for Refugees (UNCHR) on Humanitarian Assistance such as food, health care, water, sanitation, and hygiene, clothing, shelter, education and psychosocial care. This research used a qualitative research. The data collection methods used the interview and literature review. In this research, as the data sources, the respondents chosen are those which are considered appropriate and can find out the problems that will be studied to be the necessary data. The location of research is the province of Aceh precisely in the Districts of North Aceh and Kuala Langsa. The respondents are Drs. Ansyarollah MM as the secretary of Social Agency of Kuala Langsa and Rayana as a member of Women's Empowerment and Child Protection of North Aceh. The results show that the District Government of North Aceh and the District Government of Kuala Langsa have met the standard of UNHCR on Humanitarian Assistance such as food, health care, water, sanitation, and hygiene, clothing, shelter, education and psychosocial care. Meanwhile, the District Government of Kuala Langsa does not meet the standard on the non-formal education and psychosocial care. The suggestions for the future research is to expand the locations of research and add the respondents in order to obtain more complete data and analyze the standards from other international organizations. Keywords: Standard of UNHCR, Humanitarian Assistance, and Basic Needs for Refugee.